Comparison of different propeller boss cap fins design for improved propeller performances. (November 2021) - Gaggero, Stefano; Martinelli, Mattia
Highlights: Propeller Boss Cap Fins are efficient energy saving devices to answer issues enforced by IMO EEDI regulations. SBDO using RANS calculations represent a feasible design alternative for such devices. A novel solution of a "ducted PBCF" is proposed as a possible way of improving the saving performance of these devices. A complex interaction between the blade tip vortex and the vortical structures from PBCF fins is observed. The presence of the PBCF has a detrimental effect on induced pressure levels. Abstract: The performances of different Propeller Boss Cap Fins devices, designed with the aid of a Simulation Based Design Optimization approach, are analysed and compared. A novel configuration, i.e., a PBCF inside a nozzle, is investigated in an effort to mitigate possible side effects of conventional Propeller Boss Cap Fins, such as secondary vortical structures from the fins tip, increased pressure pulses and radiated noise, without excessive worsening of the beneficial effects (increased propulsive efficiency) provided by this energy saving device. Detailed analyses reveal, instead, the destabilizing effect of the hub vortical structures on the blade tip vortex evolution, determining a substantial increase of the radiated noise of this type of propulsors.